Utilizing shRNA-expressing lentivectors for viral hemorrhagic septicemia virus suppression via NV gene targeting - Pourhoseini Dehkordi, Negin; Saffar, Behnaz; Mokhtari, Azam; Asadi Samani, Leila; Amini, Azam (Frontiers in Veterinary Science, 2025)
BackgroundViral hemorrhagic septicemia virus or VHSV, is a single-stranded negative-sense RNA virus that is a member of the Rhabdoviridae family’s genus Novirhabdovirus. Its major host is rainbow trout. Severe clinical symptoms and a higher mortality rate in fish populations are caused by this virus. Regretfully, there is currently no medication or vaccination available to treat it. Recently, there has been a lot of interest in developing antiviral therapies employing interfering RNA (RNAi), particularly shRNA. This study used shRNAs targeting the NV gene of VHSV to test its effectiveness in preventing VHSV proliferation in cell culture. Using the VHSV-Fil3 strain, the appropriate oligonucleotide sequence for NV gene coding was chosen for this purpose. Subsequently, shRNA molecules were designed and synthesized with the aid of shRNA design tools. The shRNAs were transfected into HEK293T cells after being cloned into the suitable vectors using the third generation of lentiviral packaging system. The CS2-2 cell line was subsequently transduced with these shRNA-expressing lentiviruses in order to challenge the VHS virus. Finally, TCID50 was employed to calculate the viral infectious titer in order to assess the effectiveness of shRNAs.ResultsAccording to the final calculations, all shRNAs exhibited antiviral activity. When compared to the control groups, the shRNAs 1, 2, and 3 considerably lowered VHSV output in the TCID50 test (nearly 99.99, 99.99, and 99.99%, respectively, compared to cells with VHSV inoculation and nearly 99.98, 99.98, and 99.97%, respectively, compared to cells with VHSV and scrambled vector inoculation).ConclusionThus, it can be declared that RNA interference (RNAi) has the potential to be an exceptionally effective therapeutic option against viruses like VHSV.